Księgozbiory Bibliotek Studium Zagadnień Społecznych i Gospodarczych Wsi przy Katolickim Uniwersytecie Lubelskim - Nowakowska, Monika (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The Department of Social and Economic Issues of the Rural Areas at the Catholic University of Lublin, which existed between 1946 and 1949 at the Faculty of Law as well as Social and Economic Sciences at the Catholic University of Lublin, had two collections available to its students. The first one was the Library of the Department of Social and Economic Issues of the Rural Areas, and the other one was the Library of the Scientific Circle for the students of the above-mentioned department. The main initiator of the Library attached to the Department of Social and Economic Issues of the Rural Areas was the director - prof. Czesław Strzeszewski. The selection of library collections was determined by the syllabuses for the courses which were organized in the department. The content of the courses covered mainly administrative, legal, economic and agricultural issues. The department was aimed at educating civil servants, local authorities and cooperative personnel so that they could improve the functioning of rural institutions. The libraries collected books primarily from the field of social sciences (economics, sociology, pedagogy, administration and law), agricultural sciences (agronomy, agricultural engineering, horticulture) and humanities (history, literature, ethnology). The libraries also contained a small percentage of publications in the field of technical and natural sciences. The collection was primarily financed by the Catholic University of Lublin and the Ministry of Education.